Examining macroeconomic drivers of inflation: Evidence from panel ARDL and wavelet coherence approaches - Al-Amatullah, Ikhlas; Ahmad, Zaki; Hidthiir, Mohammad Helmi Bin; Mansur, Mustazar; Ali, Mohamed Ali (Asian Economic and Financial Review, 2025)
This study explored the effects of key macroeconomic variables—money supply, exchange rate, unemployment rate, and oil price—on inflation in five ASEAN countries from 1980 to 2020, using a panel ARDL model. The co-movement of this dynamic relationship was analyzed through a Wavelet Coherence approach to strengthen the findings to a certain extent. The analysis showed a positive, significant long-run link between money supply and inflation, emphasizing the need for prudent monetary policies. The absence of short-run effects of money supply on inflation underscores the importance of multidimensional policy formulation. Additionally, the positive exchange rate-inflation relationship in the long run calls for careful consideration in policy decisions. Furthermore, the negative unemployment-inflation relationship emphasizes the need for structural labor market reforms. Lastly, the significant short-term influence of oil prices on inflation warrants vigilance and sustainable energy strategies. This study is a valuable methodological and empirical addition to the existing body of knowledge on inflation dynamics, with its extensive analysis of macroeconomic determinants of inflation in ASEAN countries, using advanced econometric techniques. It bridges theoretical gaps, enriches methodological applications with wavelet coherence analysis, and delivers actionable insights for policymakers in emerging economies.